Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/medicina56090469
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanisms of Non-Traumatic Acute Brain Injury in Critically Ill Patients

Abstract: Delirium, an acute alteration in mental status characterized by confusion, inattention and a fluctuating level of arousal, is a common problem in critically ill patients. Delirium prolongs hospital stay and is associated with higher mortality. The pathophysiology of delirium has not been fully elucidated. Neuroinflammation and neurotransmitter imbalance seem to be the most important factors for delirium development. In this review, we present the most important pathomechanisms of delirium in critically ill pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 134 publications
(160 reference statements)
0
11
0
Order By: Relevance
“…In addition, an important intervention would be to work with a team of dieticians as gut microbiome imbalance or disruption of the gut-brain axis has been associated with the pathomechanism of delirium [ 71 , 72 ]. Both anesthetics used in general anesthesia and sedatives used in the ICU can change the composition of gut microbiome and contribute to neuroinflammation [ 73 ].…”
Section: The Importance Of Multidisciplinary Carementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an important intervention would be to work with a team of dieticians as gut microbiome imbalance or disruption of the gut-brain axis has been associated with the pathomechanism of delirium [ 71 , 72 ]. Both anesthetics used in general anesthesia and sedatives used in the ICU can change the composition of gut microbiome and contribute to neuroinflammation [ 73 ].…”
Section: The Importance Of Multidisciplinary Carementioning
confidence: 99%
“…Both anesthetics used in general anesthesia and sedatives used in the ICU can change the composition of gut microbiome and contribute to neuroinflammation [ 73 ]. The role of the dieticians is not only to provide balanced nutritional support for ICU patients, but also to use evidence-based structured dietary interventions to prevent delirium through intestinal interventions, enhancing the role of gut-brain axis [ 71 ] or modulating the tryptophan metabolism pathway proven important in acute brain disorders [ 74 ].…”
Section: The Importance Of Multidisciplinary Carementioning
confidence: 99%
“…e reason is that after probiotics enter the intestine, they can not only effectively ensure the balance of intestinal microbes but also restore intestinal peristalsis, reduce intestinal mucosal epithelial cell apoptosis, protect the barrier function of intestinal mucosa, and inhibit local inflammation of intestinal mucosa. Enhance the immune function of patients [18,19]. e results of the study showed that after treatment, the levels of PT and APTTof the two groups were higher than those before treatment, and the levels of FIB and DD were lower than those before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Increased kynurenine plasma levels thus precede the development and persistence of sepsis in critically ill patients (276,277), and is associated with lower survival in ICU patients (274). Moreover, elevated kynurenic acid (also a metabolite of kynurenine) is associated with myelin damage leading to neuronal and cognitive dysfunction in critical illness (278). Based on the therapeutic literature from other diseases (275,(279)(280)(281)(282), the critical illness researchers suggest inhibiting the IDO enzyme in order to curtail the production of neurotoxic kynurenine pathways metabolites.…”
Section: Addressing the Production Of Pro-inflammatory Cytokines And Inflammationmentioning
confidence: 99%